Prevalence of Musculoskeletal Complaints of Arm, Neck and Shoulder and Associated Risk Factors in Computer Office Workers - Kashif, Muhammad; Anwar, Mariam; Noor, Hafsa; Iram, Humaira; Hassan, Hafiz Muhammad Junaid (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2020)
Background The musculoskeletal complaints of the arm, neck and/or shoulder (CANS) affect the work-related tasks of workers who are sitting in front of the computer for an extended period of time and therefore lead to a reduction in productivity. The purpose of this study was to determine the prevalence of CANS and associated risk factors among computer office worker.Methodology A cross-sectional study was conducted among 773 computer workers working in different work settings located in Faisalabad Pakistan from January to August 2019. The questionnaires adopted in this survey study were previously used and consist of 2 parts; the first section for demographic information and the second part consists of the the Masstricht Upper Extremity Questionnaire (MUEQ) that was used to determine the prevalence of CANS.Results Of the 773 participants, 327 (42%) had shoulder pain, followed by neck pain 270 (35%), and the prevalence of pain in the upper arm and lower arm was 129 (17%) and 80 (10%), respectively. Those absent due to musculoskeletal problems were only 80 (10%). Females have reported overall more complaints 65% in upper extremity during the past years than male i. e. 56%. The study showed that there was a significant relationship between pain and age (years) (P=0.024), pain and work posture (P<0.001), and pain and work setting (P=0.009).Conclusion The study concluded that CANs are prevalent in office workers, predominantly among women, and that risk factors closely related to CANS are age, work setting and sitting posture.
Keywords: Musculoskeletal problems; CANS; Computer; Officer Workers; Prevalence